120 MeV swift Au9+ ion induced phase transition in ZrO2: monoclinic to tetragonal and cubic to tetragonal structure. (5th April 2023) - Lokesha, H S; Nagabhushana, K R; Singh, Fouran; Thejavathi, N R; Tatumi, Sonia Hatsue; Prinsloo, A R E; Sheppard, C J
Abstract: This study reports the effect of 120 MeV swift Au 9+ ion irradiation on the structures of monoclinic, tetragonal and cubic ZrO2, probed through x-ray diffraction (XRD) and Raman spectroscopy. Three phases of ZrO2 were prepared using the solution combustion method. The tetragonal and cubic phases of ZrO2 were stabilized at room temperature by adding 6% and 10% of yttrium ions, respectively. Both the XRD and Raman results confirm the partial phase transition from monoclinic to tetragonal, which was approximately 74%. Tetragonal ZrO2 is stable under 120 MeV Au 9+ ion irradiation. Interestingly, a phase transition from cubic to tetragonal ZrO2 was observed under 120 MeV Au 9+ ion irradiation. The roles of transient temperature, defects and strain in the lattice induced by swift heavy ions are discussed. This study reveals the structural stability of different phases of ZrO2 under swift heavy ion irradiation and should be helpful in choosing potential hosts for various applications such as inert fuel matrix inside the core of nuclear reactors, oxygen sensors and accelerators, and radiation shielding.